Improving Relay Matrices for MIMO Multi-Relay Communication Using Gradient Projection - Apriana Toding (Proceeding International Conference on Information Technology and Business, 2015)
In this paper, we design the optimal relay matricesfor multiple-input multiple-output (MIMO) relay communicationsystems with parallel relay nodes using the projected gradient(PG) approach. We show that the optimal relay amplifyingmatrices have a beamforming structure. Using the optimalstructure, the relay power loading algorithm is developed tominimize the mean-squared error (MSE) of the signal waveformestimation at the destination node. Simulation result demonstratethe effectiveness of the proposed relay amplifying matrix withmultiple parallel relay nodes using the PG approach in the systembit-error-rate performance.Index Terms—MIMO relay, parallel relay network, beamforming,non-regenerative relay, projected gradient.